Effects of Static and Dynamic LED Lighting Systems with Spectral Variations on the Morphological Growth of Sugar Apple (Annona squamosa) Seedlings - Defitrianida, Asyhuriyah Wardah (Universitas Brawijaya, 2026)
Seedling production is an important stage for tropical fruit crops, including sugar apple (Annona squamosa), and is strongly influenced by light quality. Light fluctuations in tropical environments often inhibit seedling growth, indicating the need for a more stable lighting system. This study aimed to evaluate the effects of LED design models and light spectra on the morphology of sugar apple seedlings. The experiment used a two-factor Completely Randomized Design (CRD), consisting of LED models (static and dynamic) and light spectra (blue, red, and white), with eight replications for each treatment. The study was conducted in a screenhouse with 60% shading. Observed parameters included plant height, leaf number, stem diameter, canopy width, root length, and biomass. The results showed that the static system provided the best relationship with canopy development (R² = 0.757), while the dynamic system produced higher light intensity but had the potential to cause photochemical stress. White light gave the best growth response (R² = 0.851), followed by red, whereas blue showed the lowest relationship. Correlation analysis indicated that static lighting supported more stable vegetative growth. Overall, static LED with white spectrum was the most effective combination for early growth of sugar apple seedlings under the conditions of this study and is recommended for tropical fruit seedling production.